Synthesis and Properties of Acridine and Acridinium Dye Functionalized Bis(terpyridine) Ruthenium(II) Complexes - Eberhard, Jens; Peuntinger, Katrin; Froehlich, Roland; Guldi, Dirk Michael; Mattay, Jochen (European Journal of Organic Chemistry, 2018)
We present first principle studies on the rational design of an acridine/N-methylacridinium dye (Acr/MeAcr+) substituted terpyridine ligand to investigate if these chromophores can act as triplet-energy storage units in bis(terpyridine) ruthenium(II) complexes. We studied the influence of the dye form (Acr/MeAcr+) as well as the interconnecting linker unit (none, 4-phenyl, or 5-thien-2-yl) and investigated these aspects by steady-state/time-resolved spectroscopy, cyclic voltammetry, X-ray structure analysis, and DFT calculations.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Dyes/Pigments; Electronic structure; Energy transfer; Functional organic materials; Ligand design; Ruthenium